Digital Tax Transformation and Corporate Compliance: Evidence from Indonesia’s e-Bupot Unification System - Kawuri, Sri; Alkautsar, Muslim; Putri, Marissa Disthy (Summa : Journal of Accounting and Tax, 2024)
Indonesia has advanced digital tax reforms through the e-Bupot Unification system, mandated since April 2022, to centralize withholding tax reporting (PPh 4(2), 15, 22, 23/26). This study assesses its effectiveness in improving corporate compliance—timeliness, accuracy, and error reduction—during March–June 2024. Using a quasi-experimental before–after design, data were collected from e-Bupot logs, DJP e-filing records, and taxpayer registries for 250 corporations. Indicators included on-time filing, validity of submissions, and error rates. Analysis combined descriptive statistics, paired t-tests, and regression. Results show substantial progress: on-time filing rose from 74.2% to 88.6%, validity rates from 81.5% to 93.2%, while error rates declined from 6.4% to 2.1%. Regression confirmed significant effects of PJAP integration and firm size. Larger firms and PJAP users achieved stronger compliance, whereas SMEs improved modestly, limited by IT capacity. Sectoral differences emerged, with service and e-commerce outperforming manufacturing. Consistent with OECD and IMF findings, e-Bupot demonstrates digital platforms’ effectiveness in reducing compliance gaps. While the system benefits larger firms most, SMEs require training, infrastructure support, and simplified interfaces. Policymakers should expand PJAP partnerships, adopt sector-specific approaches, and invest in digital literacy to ensure equitable outcomes. This study provides empirical evidence from a developing economy, affirming digital reforms’ role in strengthening compliance and modernizing tax governance.